Switchable phase and polarization singular beams generation using dielectric metasurfaces - Yanliang He (Nature Portfolio, 2017)
Abstract Singular beams which possess helical phase wavefront or spatially inhomogeneous polarization provide new freedom for optical field manipulation. However, conventional schemes to produce the singular beams have difficulty in realizing the flexible switch between different singular beams. In this work, we have experimentally demonstrated the capability of dielectric metasurfaces to generate three types of singular beams and switch between them at working wavelength of 1550  nm. We have shown vortex beam and cylindrical vector beam generation with single metasurface and cylindrical vector vortex beam generation with two cascaded metasurfaces. Moreover, experimental demonstration on switching cylindrical vector beam into vortex beam has also been done by combining one quarter-wave plate and a Glan laser polarizer. The experimental results match well with the analysis from the Jones matrix calculations. The average conversion efficiency of cylindrical vector beam to vortex beam was estimated to be 47.7%, which was about 2.3% lower than the theoretical prediction.